(untitled) (The Pakistan Development Review, 2020)
The paper takes an incisive shot at the systemic inadequacies that have tiptoed into the economic order of the state over time via the apparently innocuous mechanism of withholding taxes. Withholding tax—a legitimate instrument of preponing the state revenues on clearly identifiable chunks of incomes—has historically been resorted to by most states, and to that extent it should be normal with Pakistan, too. However, what has happened in Pakistan is that the tool of withholding taxation has been used as a source of revenues way too large in scale, size, scope and intensity. In addition to the pulling forward of tax collection on clearly demarcated chunks of incomes, a large number of transactions have also been roped into its nexus and then charged to tax by presumptivising gross receipts as income—a withholdingisation of the sorts not only of the tax system but of the entire economic system as a weighty portion of ubiquitous withholding taxes gets stuck into the pricing structure of the final goods and services produced in the economy rendering them price-incompetitive in the international market. This overwhelming withholdingisation of the economic system, it is argued, has been brought about by a numb state continually operating under, using a Freudian framework, the “pleasure principle” instead of the “reality principle” with political governments complacently choosing to continue harvesting quick bucks into the exchequer, pushing the extractive system into a total disarray, the society into burgeoning civil strife, and the economy to the Dutch Disease effect. JEL Classification: H1 Keywords: Withholdingisation; Withholding Taxes, Pakistan Tax System; Federal Board of Revenue; Civil Strife; Dutch Disease Effect; Cost of Collection; Tax Reform